The microcontroller technology hardware & software approach using HC11 architecture - Nik Mohd Kamil Nik Yusoff (Penerbit Universiti Malaysia Pahang, 2012)
This book is intended for use in universities or college-level, polytechnic or vocational school. In this book, students are exposed to the internal architecture of the microcontroller, various instruction sets, basic hardware design of microcontroller-based and some example of its application in today's product. To ensure the students will fully benefit from this book, various examples and hand-on project will be introduced in the book.